Coccidioides immitis Cervical Lymphadenitis Complicated by Esophageal Fistula. (23rd May 2016) - Loudin, Michael; Clayburgh, Daniel R.; Hakki, Morgan
Abstract : Coccidioidomycosis (valley fever) is caused by the dimorphic fungi Coccidioides immitis or Coccidioides posadasii . Most infections are asymptomatic or result in self-limited pneumonia; extrapulmonary dissemination via either hematogenous or lymphatic spread is rare. Here, we present a case of cervical C. immitis lymphadenitis that resulted in fistula formation to the esophagus via mediastinal extension. This case highlights a very unusual extrapulmonary manifestation of coccidioidomycosis, the difficulty in diagnosing coccidioidal infection when it is not suspected, and the importance of obtaining a thorough exposure history to assist with diagnosis.